Ringkøbing i middelalderen - Henningsen, Helle (Kuml, 2004)
Ringkøbing in the Middle Ages The last 25 years have seen frequent archaeological excavations in the medieval market town of Ringkøbing. In this paper, the author presents the results and weighs them against the written and cartographic sources in order to gain an overall picture of the emergence and development of the town during the Middle Ages (Fig. 1). Over the years, several local historians have dealt with the history of Ringkøbing. They based their investigations exclusively on the few medieval sources referring to the town, however, and the main issues they concentrated on were the reason for the town being situated exactly there, the origin of its name, its age, and whether it had grown out of an earlier settlement or had been a planned construction. In the first known reference to Ringkøbing, the town is called “rennumkøpingh,” or “the town at Rindum” (Fig. 2). Rindum, or “rennum,” was the rural parish, which had transferred some of its land to the town. A town prospect from around 1677 depicts the small town as seen from the north, with ships anchored on the fjord (Fig. 3). It gives a good impression of the number of streets and their directions. Nevertheless, the first reliable survey of the market town is from the early 19th century (Fig. 4). Ringkøbing is situated on the northern coast of Ringkøbing Fjord, on the edge of a moraine hill, well protected against floods. From the early days, Ringkøbing’s existence was inextricably linked with the navigation conditions on the fjord. Geologists have pointed out that during the Middle Ages the present islands in the tidal area south of Blåvandshuk continued further north, to Bovbjerg. This row of islands is visible on a chart from the mid-16th century (Fig. 5). On the chart, one of the islands is called “Numit,” which is interpreted as “Nyminde,” or “the new mouth.” Huge floods during the 17th century started a major process of drifting of material from the north along the coast, and the channels between the islands sanded up. Just one channel remained navigable, but it moved southward and eventually closed up completely (Fig. 6), which was a disastrous development for Ringkøbing. Nevertheless, during the Middle Ages, ships could still pass unhindered from the sea into the fjord and to Ringkøbing, where they could trade and take in supplies and water. Ringkøbing is situated in an area which has been inhabited since the last Ice Age, and which was especially rich during the Iron Age. By the mid-13th century the area was divided into districts and parishes, and the market town sprouted up in the middle of a well functioning agricultural region. The first actual excavation took place in Ringkøbing in 1978, when the property of Vester Strandgade 14 was investigated by Ringkøbing Museum. An area measuring 44 square metres was examined, and the excavation revealed part of the medieval town (Fig. 7). At the bottom of the excavated area, several furrows observed in a 15 to 20-cm thick humus layer indicated that the area had been farmed right up until the beginning of the activities there in the medieval period. Of the two ditches registered in the area, the earlier one had been dug into the ploughed field, whereas the later ditch was situated approximately in the middle of the medieval culture layer (Fig. 8). Twenty-three post-holes were found, but unfortunately their relationships to each other could not be determined. An extensive layer with a 3.4-metre diameter turned out to be the remains of a well, the shaft of which had been built from granite boulders (Fig. 9). A small bronze buckle was found at the bottom of the well (Fig. 10), and several sherds of imported pottery from around 1300 were found in the filling around the well shaft. The layer sequence was visible in the walls, with the yellow-brown moraine gravel at the bottom, then the above-mentioned humus layer with furrows, and then the homogeneous, grey, medieval culture layer. Above this an earthen floor from the 17th century was visible in several places. The upper layer, with a thickness of c.60 cm, was modern. The medieval layer contained large amounts of pottery sherds, mainly from locally produced grey-brown globular vessels. The rim sherds were from two main pottery types, A and B. Type A, which constitutes the largest group, has the classical, almost S-shaped rim (Fig. 12), whereas type B is characterized by an outward-folded edge creating a flat inner rim (Fig. 13). Both types exist concurrently throughout the medieval culture layer. The glazed pottery sherds represent two types, locally produced earthenware (Fig. 14), and imported pottery. Both types were present in the Vester Strandgade excavation. Of the imported sherds, 39 are from green-glazed jugs with a “raspberry” decoration (Fig. 15). These jugs were produced in the Netherlands around 1300. Sherds from German stoneware found in the medieval layer date from the same time (Fig. 16). The Vester Strandgade excavation was followed by several large and small investigations in the town centre (Fig. 17). “Dyekjærs Have” contained several traces of medieval structures, for instance a large number of post-holes, some of which were from a small building. The pottery material was abundant and consisted mainly of sherds from greyish-brown globular vessels (Fig. 18), but there were also sherds from imported and locally manufactured jugs. Other important town excavations include that of Marens Maw’, where the numerous traces of medieval structure included a row of post-holes interpreted as the outer wall of a house, and the excavation of Øster Strandgade 4, which revealed a late medieval turf-built well (Fig. 19). The excavation of Bojsens Gård also gave interesting results. It was very close to the street, and in this area the medieval culture layer had a depth of up to 60 cm. A ditch dug into the ploughed medieval field represented the earliest activity on this spot. Several structural traces reflected a continuous settlement going back to the early days of the town. Here, too, sherds from globular vessels dominated, but glazed ceramics and stoneware were also represented. The written sources from the Middle Ages reveal nothing about the medieval appearance of the town. The archaeological excavations, on the other hand, have shown that the settlement consisted of houses made from posts dug into the ground, probably half-timbered constructions with wattle-and-daub outer walls, earthen floors, and thatched roofs. The archaeological excavations have also revealed that Ringkøbing sprang up on a ploughed field during the second half of the 13th century. There are no signs of any settlement prior to this, and it is most likely that the town was laid out all at once according to a fixed town plan. No building traces were found in the streets, on Torvet (the market square), on Kirkepladsen (the church square), or on Havnepladsen (the harbour square), and so these squares must have been planned as such from the beginning. The numerous grooves and ditches are interpreted as boundary markers made when the plots were first established. The earliest ones are dug into the ploughed field, and so they must indicate the very first land-registration of the town. In order to found the new market town, an oblong part of Rindum parish had to be confiscated, and the town was marked out in the western part of this as an area measuring approximately 550 by 250 metres (Fig. 20). The streets were laid out in the still existing regular network. There was no harbour, and the ships would anchor in the shallow water off the town. Goods were transported by barge or horse-drawn carriage. In the town centre the market square was laid out, and behind it the square by the church. Ringkøbing’s church is a small Gothic brick building from around 1400. The townsmen probably used the parish church in Rindum during the first 150 years. At the time when Ringkøbing was founded, the Crown was establishing several small coastal towns throughout the kingdom. There was a notable lack of towns along the west coast of Jutland, and the founding of Ringkøbing probably represents a wish to fill this vacuum. At the same time, it was a friendly gesture directed towards the merchants from Northwest Europe whose large merchant ships sailed along the west coast on their way to and from the major markets in the Baltic. It was in the king’s interest to control the trade in the country, as it enabled him to levy taxes and to oppose the Hanseatic League’s attempt to monopolise foreign trade. Life in medieval Ringkøbing was based on trade and crafts, and the king controlled both through his assignment of privileges. The first preserved trade licence concerning medieval Ringkøbing is from 1443, but that document is in fact a confirmation of a privilege previously granted. The archaeological excavations and the written sources have informed us that the town’s trade interests lay across the North Sea. The town’s own merchants travelled overseas, and foreign merchants passed through. Foreign goods such as glazed jugs, stoneware jugs, and woollen cloth were imported from the Netherlands, Flanders, and Germany. The sources also indicate that a hinterland reaching far into Jutland used Ringkøbing for disembarkation. After the Middle Ages, the sources describe Ringkøbing as a small town, at times rather poor, which often had to ask permission to postpone the tax payments for which it was liable. The earliest depictions and maps also give the impression of a small town taking up less space than it did during the Middle Ages (Fig. 21). It will be interesting to learn whether future excavations in Ringkøbing will radically change the picture of the town presented here. Helle Henningsen Ringkøbing Museum Translated by Annette Lerche Trolle